Ação antiespasmódica gastrintestinal e potencial efeito anti-inflamatório do cinamato de metila em ratos sujeitos a modelo de colite por ácido acético - Lima Júnior, Francisco José Batista de (2013)
It was previously shown that the essential oil of Ocimum micranthum (EOOM), and its major constituent, methyl cinnamate (MC), have myorelaxant action on tracheal smooth muscle, airway anti-inflammatory and anti-nociceptive on rodents. The present work aimed to evaluate the antispasmodic and anti-inflammatory potential of MC on gastrointestinal tissues from rats subjected to acetic acid-induced colitis model. EOOM inhibited carbamylcholine- (CCh; 1 M) and KCl-induced (60 mM) contractions in stomach fundus strips with IC50 of 91.9 g/mL and 46.8 g/mL, respectively. It significantly reduced the basal tonus as well as the spontaneous contractions in duodenum. The isomers (Z)- or (E)-MC also inhibited CCh and KCl contractions in fundus, antrum, duodenum and colon strips, without differences between the effects caused by the isomers in each segment. MC significantly inhibited CCh in lower concentration in comparison with KCl, but with decreased potency if compared to atropine. (E)-MC inhibited intracellular calcium stores-dependent contractions, and its effect seems not to involve the activity of the nitric oxide synthase or the opening of potassium channels. Analyzed by confocal microscopy, freshly dissociated colon cells showed reduced basal cytosolic calcium levels (60%) after (E)-MC (600 M) exposure. In vivo, a first dose of (E)-MC (50 mg/kg) did not affect gastric contractions, but following a second dosage (50 mg/kg) administered a half an hour later, it reduced gastric contractions for 10 minutes. Colitis was induced by rectal instillation of acetic acid 5%. Sham group received only saline in instillation, while treated groups, beyond acid instillation, received (E)-CM 50 mg/kg/day p.o. or prednisolone 1 mg/kg/day p.o. during three days. Acetic acid instillation induced colitis that was macroscopically confirmed, leukocytosis, increased interleucin-1β and functional response loss due to voltage operated calcium channel disorder. These parameters were recovered by (E)-MC or prednisolone. Therefore, EOOM and CM have in vitro antispasmodic effect on rat gastrointestinal tract. The effect of CM involves reduction of the intracellular levels of calcium being independent of the nitric oxide synthase and potassium channels. CM has anti-inflammatory action comparable to prednisolone in magnitude.